Medieval Renaissance Baroque: A Cat's Cradle for Marilyn Aronberg Lavin - Lavin, Marilyn Aronberg; Levine, David A.; Freiberg, Jack (Italica Press studies in art and history, 2010)
"Reflects Marilyn Aronberg Lavin's innovative work in art and cultural history in both the print and digital realms. Contributors: Kirk Alexander, Horst Bredekamp, Nicola Courtright, David Freedberg, Jack Freiberg, Marc Fumaroli, David A. Levine, Daniel T. Michaels, Elizabeth Pilliod, Debra Pincus, Gary Schwartz. Seventy-seven illustrations, bibliography of Lavin's works, index"--Provided by publisher.
Keywords: Art, European; dept.art; faculty_collection